Vascular Injury of Penetrating Trauma of the Extremities - Yeliz Simsek; Aysenur Gur (Emergency Medicine International)
Conclusion: Vascular injury was present in all cases that had positive hard signs. CTA imaging and vascular intervention are not necessary in patients who exhibit no hard and/or soft indicators during a thorough physical examination.